The nursing research landscape in Malaysia: a scoping review of trend and gaps in literature (2010-2019) - Hazlinda Jamalludin; Krishanthini Jeyabalan; Hasmein Mohd Razali; Siswanita Anak Main; Rosnah Mohidin; Catherina Ak Guan; Roslinda Abu Sapian; Nurul Syarbani Eliana Musa; Sharifah Zawani Syed Ahmad Yunus; Wei Hong Lai; Nur Khairul Bariyyah Mohd Hatta; Rozila Harun; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Globally, there is a growing emphasis on the direct implementation of research findings to daily practice and their seamless incorporation into routine nursing care. This emphasis stems from the realisation that evidence based practise is essential to enhancing patient outcomes and advancing the nursing profession. Consequently, the imperative to conduct nursing research has emerged as a key priority. Hence, this study examines the nursing research landscape in Malaysia. This scoping review was conducted in accordance to the Arksey and O’Malley’s seminal framework utilising three (3) electronic databases (PubMed/MEDLINE, ScienceDirectand CINAHL) for journal articles published between 2010 to 2019. Systematic searches yielded 949 articles for preliminary reviewand after removing duplicates and irrelevant publications, 42 articles were included for final analysis and interpretation. In general, the majority of the reviewed articles were published in the nursing management category (28.6%)and 30.9% were descriptive cross-sectional designs. In addition, the majority of examined articles (97.6%) were written by authors affiliated with the Ministry of Educationand 78.6% of the reviewed articles utilised nursing models or theories as their theoretical framework. Furthermore, the majority of reviewed articles address the improvement of nursing service and recommend prioritising incentives and comfortable work environments, as well as incorporating education on patients’ transitional experiences and increasing the quantity of critically ill patient-related content in nursing curricula. The nursing research landscape in Malaysia is characterised by richness and diversity; however, more research activities on the identified gaps are encouraged. Moreover, given the diversity of research topics and methodologies, nursing research in Malaysia has the potential to make significant contributions to the nursing profession and healthcare in general. Future efforts should focus on updating searches to study research trends across the pre-pandemic, during-pandemicand post-pandemic periods. These studies should also prioritize the inclusion of local journal publications, such as the Malaysian Journal of Nursing, to ensure a comprehensive and detailed examination of the country’s evolving research landscape.